1981
DOI: 10.1080/01639625.1981.9967563
|View full text |Cite
|
Sign up to set email alerts
|

Retardation and the burden of stigma

Abstract: An exploratory study of parents with mentally retarded children, plus previous research by others, suggests three hypotheses on problems of stigma that were systematically tested in mailed questionnaires returned by 319 mothers of seriously retarded children. Response to a series of statements were factor analyzed to form a scale of "stigma."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…This distribution of child gender is not unusual when dealing with special-needs children. The greater prevalence of developmental disabilities among boys is probably a result of gender-linked recessive conditions (Tyson & Favell, 1988) and society's higher expectations for boys' intellectual competence than for girls' (Levinson & Starling, 1981;Marsh, 1992;Tyson & Favell, 1988). Of the various diagnoses, 33% of the children had Down's syndrome, 3 1% had autism, 23% had developmental delays, and 13% had other etiologies of cognitive delays (e.g., cerebral palsy, fragile X syndrome, congenital hydrocephalus).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This distribution of child gender is not unusual when dealing with special-needs children. The greater prevalence of developmental disabilities among boys is probably a result of gender-linked recessive conditions (Tyson & Favell, 1988) and society's higher expectations for boys' intellectual competence than for girls' (Levinson & Starling, 1981;Marsh, 1992;Tyson & Favell, 1988). Of the various diagnoses, 33% of the children had Down's syndrome, 3 1% had autism, 23% had developmental delays, and 13% had other etiologies of cognitive delays (e.g., cerebral palsy, fragile X syndrome, congenital hydrocephalus).…”
Section: Participantsmentioning
confidence: 99%
“…Perceived stigma. Perceived stigma associated with the child's diagnosis was assessed with an eight-item measure adapted from two previously used measures (Crandall, 1991;Levinson & Starling, 1981; see Appendix A for instrument).…”
Section: Instrumentsmentioning
confidence: 99%
“…There are important theoretical and practical imperatives towards finding a new way of studying stigma. It has been widely acknowledged in recent years that people with disabling conditions and their families may be as greatly handicapped by stigmatizing community attitudes as by the disability itself (see for example, Ablon, 1981;Darling & Darling, 1982;Davis, 1977;Gibbons, 1985;Levinson & Starling, 1981;Scott, 1981;Sutherland, 1981). Therefore, it is very important to understand the impact of stigma on the life experience of children who are mentally retarded and their families and the conditions under which it may be alleviated.…”
Section: Introductionmentioning
confidence: 99%
“…Both Birenbaum (1970) and Levinson and Starling (1981), for example, reported that parents of mentally retarded children experienced strained relationships and social exclusion. Sack, Seidler, and Thomas (1976) found that the spouses of imprisoned parents suffered disrupted social relations and that their children were teased by peers.…”
mentioning
confidence: 96%